Crude Extracts of Talaromyces Strains (Ascomycota) Affect Honey Bee (Apis mellifera) Resistance to Chronic Bee Paralysis Virus - Vocadlova, Katerina; Lamp, Benjamin; Benes, Karel; Matha, Vladimir; Lee, Kwang-Zin; Vilcinskas, Andreas (Viruses, 2023)
Viruses contribute significantly to the global decline of honey bee populations. One way to limit the impact of such viruses is the introduction of natural antiviral compounds from fungi as a component of honey bee diets. Therefore, we examined the effect of crude organic extracts from seven strains of the fungal genus Talaromyces in honey bee diets under laboratory conditions. The strains were isolated from bee bread prepared by honey bees infected with chronic bee paralysis virus (CBPV). The antiviral effect of the extracts was also quantified in vitro using mammalian cells as a model system. We found that three extracts (from strains B13, B18 and B30) mitigated CBPV infections and increased the survival rate of bees, whereas other extracts had no effect (B11 and B49) or were independently toxic (B69 and B195). Extract B18 inhibited the replication of feline calicivirus and feline coronavirus (FCoV) in mammalian cells, whereas extracts B18 and B195 reduced the infectivity of FCoV by ~90% and 99%, respectively. Our results show that nonpathogenic fungi (and their products in food stores) offer an underexplored source of compounds that promote disease resistance in honey bees.
Keywords: Ascomycota; Cats; antiviral activity; fungal extracts; Paralysis; RNA-viry; koronavirus koček; mycotoxins; Coronavirus, Feline; antivirové látky; CBPV; kočky; zvířata; Mammals; Talaromyces; RNA Viruses; savci; včely; Antiviral Agents; Bees; Apis mellifera; paralýza; Animals